Risk assessment of the adverse impact of industrial synthesis of benzodiazepine drugs on human health - L. G. Gorokhova; D. V. Surzhikov; N. N. Mikhailova; N. A. Martinova (Acta Biomedica Scientifica, 2013)
Among the occupational and work-related diseases of employees in pharmaceutical industry the leading positions belong to the diseases caused by long-term work under the conditions of relatively low concentrations of hazard substances. The study and evaluation of risks will eliminate or reduce the impact, thereby, enhancing the quality of life. Synthetic drugs - benzodiazepine derivatives by the values of middle-lethal doses are substances of the 111 class of hazard and cause slight irritating effect to the skin and mucous membranes of the eyes; skin-resorptive and sensitizing effects have not been identified. For the studied benzodiazepine derivatives the safe exposure levels have been approved in the following values: nozepam -1 mg/m3; mezapam - 0.3 mg/m3; sibazon - 0.2 mg/m3; alprazolam - 0.1 mg/m3. On the base of the toxicological studies the parameters of the hazardous effects on the body have been identified allowing for a final risk characterization. The article presents the results of the calculation of the potential dose that may be received by the employee during the working shift in the synthesis of products of this series. Calculation of safe level of exposure is based on a threshold concentration of substances. Drags risk factors by inhalation have been calculated by comparing the value of the potential dose of a xenobiotic received for one shift by inhalation with its level of safe effect under the same route of exposure. The estimated hazard ratios for the studied substances demonstrate a low probability of adverse effects on the workers during the production of nozepam and alprazolam. High risk of negative impact on the health of workers has been identified during the production of sibazon and mezapam. This information can then be used to control the working environment during the synthesis of drugs - benzodiazepine derivatives, aimed at creating a safe working environment and, consequently, improving the workers' life quality.